Characterization of third exonic region of POU1F1 gene in the Osmanabadi breed of goat - PAWAR, VIKRANT; SAWANE, MAHADEO; ZUNJARRAO, KALPESH; DOIPHODE, AAKASH (The Indian Journal of Animal Sciences, 2021)
The POU1F1 gene has been identified as one of the major gene for productivity, and its polymorphism is known to be associated with important production traits of various livestock. The present study was designed to investigate POU1F1 (exon-3) gene polymorphism and its association with body weight in Osmanabadi goat (n=217). The PCRSSCP and DNA sequencing revealed single ‘C’ > ‘T’ transition at nucleotide position 42 in the third exonic region (225 bp) POU1F1 gene of Osmanabadi goat. Genotyping revealed ‘TT’ and ‘CC’ genotypes with predominance of ‘C’ allele in the Osmanabadi goat population. Though no association between the said SNP and body weight was observed, these findings can be extended to find the genetic variability of POU1F1 gene associated with growth traits of various Indian goat breeds.